Effectiveness and impact of community-based health insurance on health service utilization in northwest Ethiopia: a quasi-experimental evaluation - Fetene, Samrawit Mihret; Mengistu, Mezgebu Yitayal; Aschalew, Andualem Yalew (Frontiers in Public Health, 2023)
Background: Addressing the health challenges of the poor population in Ethiopia is still a huge problem. In that regard, the government piloted the community-based health insurance (CBHI) in 2011 in few districts and subsequently scaled up. However, the effectiveness of the program on health services utilization and its impact was not well explored. Thus, we evaluate the effectiveness of CBHI towards health services utilization and its impact in northwest Ethiopia.: A quasi-experimental matched comparison group evaluation design with sequential explanatory mixed methods was employed. To evaluate the CBHI program, the effectiveness and impact dimensions from the Organization for Economic Cooperation and Development framework were used. A multistage sampling technique was used to select a total of 332 households enrolled in the CBHI program and 341 comparison households who did not enrolled in the program were randomly selected. A structured interviewer administrated questionnaire was used to evaluate the effectiveness and impact of CBHI on health service utilization. The Propensity score matching model was employed for the estimation of the effect of CBHI program on health service utilization. Challenges for program achievement towards health service utilization were explain through qualitative and the data were analyzed thematically.The evaluation showed that 1.3 visits per capita per year of health services utilization among CBHI members. Households enrolled in CBHI increase health service utilization by 6.9 percentage points (ATT= 0.069; 95% CI: 0.034, 0.114). There was an improvement in health service utilization after the introduction of CBHI, however, there are challenges; (i) shortage of human resources (ii) stock-out of drugs and medical supplies, (iii) long waiting time at services deliveries, and claims to reimbursement of health expenditure, which generated from the qualitative interviews, that limit the program success towards health service utilization.The CBHI program contributed to health service utilization improvement among CBHI members. However, the health services utilization rate among CBHI members is still less than the target stated for the program and also the WHO recommendation. Therefore, the finding of this evaluation can be used by program implementer, policy maker and other stakeholders to overcome the identified challenges and to fasten the program success.